DNA methylation changes induced by long and short photoperiods in Nasonia - Pegoraro, Mirko; Bafna, Akanksha; Davies, Nathaniel J.; Shuker, David M.; Tauber, Eran (Genome Research, 2016)
Many organisms monitor the annual change in day length and use this information for the timing of their seasonal response. However, the molecular mechanisms underlying photoperiodic timing are largely unknown. The wasp Nasonia vitripennis is an emerging model organism that exhibits a strong photoperiodic response: Short autumnal days experienced by females lead to the induction of developmental arrest (diapause) in their progeny, allowing winter survival of the larvae. How female Nasonia control the developmental trajectory of their offspring is unclear. Here, we took advantage of the recent discovery that DNA methylation is pervasive in Nasonia and tested its role in photoperiodism. We used reduced representation bisulfite sequencing (RRBS) to profile DNA methylation in adult female wasps subjected to different photoperiods and identified substantial differential methylation at the single base level. We also show that knocking down DNA methyltransferase 1a (Dnmt1a), Dnmt3, or blocking DNA methylation pharmacologically, largely disrupts the photoperiodic diapause response of the wasps. To our knowledge, this is the first example for a role of DNA methylation in insect photoperiodic timing.